TMPRSS2–ERG rearrangement in dominant anterior prostatic tumours: incidence and correlation with ERG immunohistochemistry. Issue 2 (23rd May 2013) - Gopalan, Anuradha; Leversha, Margaret A; Dudas, Maria E; Maschino, Alexandra C; Chang, Jeremy; Al‐Ahmadie, Hikmat A; Chen, Ying‐Bei; Tickoo, Satish K; Reuter, Victor E; Fine, Samson W
<x xml:space="preserve">Abstract</x> Aim To study prostate cancer zonal differences in TMPRSS2–ERG gene rearrangement. Methods and results We examined 136 well‐characterized dominant anterior prostatic tumours, including 61 transition zone (TZ) and 75 anterior peripheral zone (PZ) lesions, defined using strict anatomical considerations. TMPRSS2–ERG FISH and ERG protein immunohistochemistry were performed on tissue microarrays. FISH results, available for 56 TZ and 71 anterior PZ samples, were correlated with ERG staining and TZ‐associated 'clear cell' histology. Fewer TZ cancers (four of 56; 7%) were rearranged than anterior PZ cancers (18 of 71; 25%) (P = 0.009); deletion was the sole mechanism of TZ cancer rearrangement. ERG protein overexpression was present in 4% (two of 56; both FISH+) and 30% (21 of 71; 17 FISH+) of TZ and anterior PZ tumours, respectively. 'Clear cell' histology was present in 21 of 56 (38%) TZ and eight of 71 (11%) anterior PZ tumours. Seven per cent of cancers with and 21% without this histology had rearrangement, regardless of zonal origin. Conclusions TMPRSS2–ERG rearrangement occurs in dominant TZ and anterior PZ prostate cancers, with all rearranged TZ cancers in this cohort showing deletion. ERG immunohistochemistry demonstrated excellent sensitivity (86%) and specificity (96%) for TMPRSS2–ERG rearrangement. TMPRSS2–ERG fusion is rare in TZ tumours and present at a low frequency in tumours displaying 'clear cell' histology.